MULTICRITERIA APPROACH TO RURAL TOURISM DEVELOPMENT IN REPUBLIC OF SRPSKA - Nedeljković, Miroslav; Puška, Adis; Krstić, Svetozar (Economics of Agriculture, 2022)
The purpose of this paper is to examine the current state of rural tourism in Republic of Srpska as well as to provide guidance and recommendations for the development of this form of tourism. The used model approach expert opinion and, on this occasion, the DEX method of multicriteria decision-making was used. With this model, an assessment of rural tourist capacities is carried out on a random sample of four tourist facilities. The reason for the results obtained in this way is that the observed facilities have adequately used the natural resources available to Republic of Srpska. In addition, recommendations and guidelines are given in order to further develop this type of tourism in Republic of Srpska. The presented model offers an innovative approach in the assessment of current and potential tourist facilities. For this reason, it should be used in future research.